Human DNA polymerase α interacts with mismatch repair proteins MSH2 and MSH6. Issue 23 (16th November 2016) - Itkonen, Harri M.; Kantelinen, Jukka; Vaara, Markku; Parkkinen, Sinikka; Schlott, Bernhard; Grosse, Frank; Nyström, Minna; Syväoja, Juhani E.; Pospiech, Helmut
Abstract : High fidelity of genome duplication is ensured by cooperation of polymerase proofreading and mismatch repair (MMR) activities. Here, we show that human mismatch recognizing proteins MutS homolog 2 (MSH2) and MSH6 copurify and interact with replicative Pol α. This enzyme also is the replicative primase and replicates DNA with poor fidelity. We show that MSH2 associates with known human replication origins with different dynamics than DNA polymerase (Pol α). Furthermore, we explored the potential functional role of Pol α in the mismatch repair reaction using an in vitro mismatch repair assay and observed that Pol α promotes mismatch repair. Taken together, we show that human Pol α interacts with MSH2‐MSH6 complex and propose that this interaction occurs during the mismatch repair reaction. Abstract :